2017
DOI: 10.1093/femspd/ftx101
|View full text |Cite
|
Sign up to set email alerts
|

High-fat-diet-induced obesity upregulates the expression of lymphoid chemokines and promotes the formation of gastric lymphoid follicles after Helicobacter suis infection

Abstract: Helicobacter suis colonizes the stomachs of a variety of animals, including humans, and is more likely than other Helicobacter species to induce gastric mucosa-associated lymphoid tissue lymphoma. Obesity is a low-grade chronic inflammatory state in which the induction of a chemokine network contributes to a variety of diseases. However, the effect of obesity on the development of gastric MALT in the presence of H. suis infection remains unclear. Here, we reveal that high-fat-diet-induced obesity upregulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These may cause the dysfunction of the vascular–endothelial barrier, the development of a pathological inflammatory response, macrophage infiltration and activation, and the proliferation of smooth muscle cells that are involved in plaque formation [ 38 ]. Kiss et al (2006) [ 39 ] showed that ROS modulate the activity of nuclear poly (ADP-ribose) polymerase (PARP), which may result in the reduction of the relaxing properties of the blood vessels [ 39 ]. Akbas et al (2010) [ 40 ] revealed that in H. pylori infected subjects, the activity of serum paraoxygenase-1 is related to carotid intima media thickness [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These may cause the dysfunction of the vascular–endothelial barrier, the development of a pathological inflammatory response, macrophage infiltration and activation, and the proliferation of smooth muscle cells that are involved in plaque formation [ 38 ]. Kiss et al (2006) [ 39 ] showed that ROS modulate the activity of nuclear poly (ADP-ribose) polymerase (PARP), which may result in the reduction of the relaxing properties of the blood vessels [ 39 ]. Akbas et al (2010) [ 40 ] revealed that in H. pylori infected subjects, the activity of serum paraoxygenase-1 is related to carotid intima media thickness [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. suis is also associated with increased levels of lymphotoxin (LT)-α and -β in the stomach of mice ( 88 ). These cytokines are not only involved in the generation of follicular dendritic cells ( 89 ), but also regulate neuronal and glial lineage differentiation ( 90 ).…”
Section: Helicobacter Suis and The Microbiome–gut–brain Axismentioning
confidence: 99%
“…Blocking lymphotoxin in experimental autoimmune encephalomyelitis (EAE), a mouse model of MS, reduces disease symptoms, which is accompanied with lower levels of the chemokine CXCL13 ( 92 ). This chemokine plays a role in the recruitment of B-cells and its expression is increased in the stomach after H. suis infection in both pigs, mice, and gerbils ( 72 , 81 ), as are other chemokines such as C-X-C motif chemokine receptor (CXCR) 7, 15 and 4, C-C motif chemokine ligand (CCL) 19 and 21, and C-X-C motif chemokine ligand 12 (CXCL12) ( 88 ). In MS, higher levels of CXCL13 have been observed in B-cell aggregates in the inflamed meninges ( 92 ) and correlate with demyelination, neural cell loss, and rapid disease progression ( 93 ).…”
Section: Helicobacter Suis and The Microbiome–gut–brain Axismentioning
confidence: 99%
“…Over the last year, further evidence has emerged on the role of H. suis in the pathogenesis of gastric mucosa‐associated lymphoid tissue (MALT) lymphoma. Zhao et al revealed that high‐fat diet‐induced obesity upregulated the expression of lymphoid chemokines in the stomach, potentially via a mechanism that involves the activation of the nuclear factor kappa B (NF‐κB) signaling pathway. Floch et al showed that in APRIL Tg‐infected mice leukocyte infiltrates were composed of B cells and highlighted the importance of APRIL in the development of gastric lymphoid infiltrates.…”
Section: Pathogenesis Of Infections With Non‐helicobacter Pylori Helimentioning
confidence: 99%